Assessing the Cybersecurity Literacy Proficiency among Bachelor’s Degree Students in Nepal (OCEM Journal of Management, Technology & Social Sciences, 2026)
As Nepal’s higher education system is being shifting toward digitalization, the importance of cybersecurity literacy among the bachelor students has never been greater. With growing threats and risks like phishing, scams and data breaches, it is essential to understand how well students are prepared to protect themselves in this digitalized environment. Improving the cybersecurity literacy in higher education can play very important role in preparing students for a secure digital future and reduce the unwanted exposure to digital threats, scams and risks. Our study aims to examine the cybersecurity awareness level among bachelor-levelstudents in Nepal. Understanding their knowledge, attitude, and day-to-day practices is our main aim. Our study employed a quantitative survey method to collect data from two hundred and ten ( N = 221) samples. The survey method was used to gather students’ opinions and experiences regarding digital threats, their efforts to mitigate these threats, and the impact of cybersecurity education in their day to day online presence.The descriptive statistics was used to analyse the collected data, along with the application of a binary logistic regression model. The findings reveal that Nepalese bachelor level students have poor awareness about cybersecurity threats which show a noticeable gap in cybersecurity education, spreading vulnerabilities and limited impact of current training initiative. The result further highlights that there was no association between cybersecurity awareness level and gender. The results importantly that students are familiar with common cyberattacks, understand how they manage the risks, and the effectiveness of current cybersecurity education efforts. By examining key factors that influence cybersecurity awareness, it offers benefits to educational, social and technical institutions, policymakers, and cybersecurity professionals to understand the current level cybersecurity awareness of youths.